Penerapan Metode Ceramah dalam Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam di SMP Hidayutullah Medan - Dahri Putri, Yolan; Setiawan, Muhammad Raihan; Yusmeini, Dinda (Yayasan Rahmat Islamiyah, 2024)
This study aims to evaluate the effectiveness of the lecture method in enhancing students' learning outcomes in Islamic Religious Education at SMP Hidayatullah Medan. Through a quantitative approach, the study involved collecting data on students' performance and engagement before and after implementing the lecture method. A total of 80 students participated, divided into experimental and control groups. The findings reveal that the lecture method significantly improved students' comprehension of Islamic education topics, especially in aspects that required a deep understanding of religious knowledge and values. Teachers observed a notable increase in students' participation and focus during lessons. This method also provided structured guidance, making complex Islamic teachings more accessible. Thus, the study concludes that the lecture method, if applied effectively, can positively influence students' academic achievements in Islamic Religious Education. However, it suggests that a balanced approach, integrating other interactive techniques, may enhance its effectiveness further.